I guess you're just supposed to write out (2 + i)^2.
(2+i)^2 = (2+i)(2+i)
= 4 + 4i + i^2
= 4 + 4i -1
= 3 + 4i.
2007-06-13 07:05:23
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
If you wish to solve for 'c' and 'd', we have:
c + di = (2 + i)^2
= (2 + i)(2 + i) = 4 + 4i + i^2
= 4 + 4i - 1 = 3 + 4i.
Equating real and imaginary parts on the two sides:
c = 3 and d = 4.
2007-06-13 07:09:45
·
answer #2
·
answered by quidwai 4
·
0⤊
0⤋
(2 + i)² =
2² + 2•2i + i² =
4 + 4i - 1 =
3 + 4i
so c = 3, d = 4
2007-06-13 07:05:52
·
answer #3
·
answered by Philo 7
·
1⤊
0⤋
c + di = (2 + i)^2
c + di = 2^2 + 2*2*i + i^2
c + di = 4 + 4i - 1
c + di = 3 + 4i
The numbers on left side and right side are both complex.
Two complex numbers are equal only if their real and imaginary parts are separately equal.
Here, for (c + di) real part = c and imaginary part = d
and for (3 + 4i) real part = 3 and imaginary part = 4
So c = 3, d = 4
2007-06-13 07:06:32
·
answer #4
·
answered by psbhowmick 6
·
0⤊
0⤋
(2 + i).(2 + i) = 4 + 4i - 1 = 3 + 4i
c = 3
d = 4
2007-06-13 07:06:19
·
answer #5
·
answered by Como 7
·
0⤊
0⤋